Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Perinatal exposure to delta-9-tetrahydrocannabinol (THC) alters goal-directed behavior and dopamine functioning in wistar rats - Monica S. Carbajal; Rebecca C. Crenshaw; Victoria E. Williams; Laura G. Billings; Chelsea M. Dixon; Deranda B. Lester; Helen J. K. Sable (Psychopharmacology, 2026)
Rationale Cannabis use during 2021pregnancy is common as many pregnant women consider cannabis as a safe way to alleviate symptoms associated with pregnancy because it is “natural”. However, clinical evidence links perinatal cannabis exposure to externalizing behavior in offspring. In preclinical research, most studies focus on exposure to the psychoactive constituent of cannabis, delta-9-tetrahydrocannabinol (THC). THC is lipophilic, allowing it to cross the placental barrier and be secreted in maternal milk, thereby exposing the fetus/neonate. Objective We used operant procedures to measure motivation and impulsivity in adult offspring perinatally exposed to THC. Methods Dams were orally exposed to 0 or 5 mg/kg/day THC daily from 14 days prior to breeding to postnatal day (PND) 14. Differential reinforcement of high rates (DRH) and differential reinforcement of low rates (DRL) of responding tasks were used to examine motivation and impulsive action. We also measured dopamine (DA) functioning in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) via in vivo fixed potential amperometry in littermates of rats that completed behavioral testing. Results Perinatal THC exposure had minimal effects on impulsive action measures during DRL 15s. Rather, perinatal THC exposure decreased DRL 15s burst responses and completed trials in both sexes, and reinforcers earned in THC-exposed males. Decreased lever presses during DRH were observed in both sexes perinatally exposed to THC, as well as fewer reinforcers in THC-exposed males. THC exposure did not alter baseline DA release in the NAc or mPFC, but did attenuate the dopaminergic response to cocaine in the NAc. Conclusions These results suggest perinatal exposure to THC can decrease motivation to work for reinforcers during high-effort tasks, that this effect may be more pronounced in males, and that the “amotivational state” resulting from perinatal THC exposure may be due to reinforcer devaluation. Keywords : oral THC, developmental neurotoxicology, amotivational syndrome, mesocorticolimbic dopamine.

Short-wave fadeout on mars: Radio absorption in the dayside martian ionosphere enhanced by solar flares - Y. Harada; B. Sánchez-Cano; M. Lester; A. Ippolito (Icarus, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Internal organs and body tissues of free-swimming whale sharks (Rhincodon typus) imaged using underwater ultrasound - M. G. Meekan; F. Thompson; K. Brooks; R. Matsumoto; K. Murakumo; E. Lester; A. Dove; B. Hopper (Frontiers in Marine Science, 2024)
Ultrasound imaging can be used as an effective tool to measure the reproductive status and condition of sharks. This usually requires restraint of the subject, which is not feasible in the wild when the target species is of conservation concern and very large, as is the case for whale sharks. Our study invoked a behavioral response in free-swimming whale sharks that allowed snorkelers to image internal organs and structures using a submersible ultrasound scanner linked to an iPhone in an underwater housing. We were able to reliably locate and monitor the heart and other internal organs inside the body cavity, structures inside the head, and image skin and muscle in the dorsal surface of the sharks. The technique is evaluated as a means for assessing the condition and reproductive status of free-swimming whale sharks.

Associations between neighborhood characteristics and child well-being before and during the COVID-19 pandemic: A repeated cross-sectional study in the Environmental influences on Child Health Outcomes (ECHO) program - Xueying Zhang; Courtney K. Blackwell; Janet Moore; Shelley H. Liu; Chang Liu; Christopher B. Forrest; Jody Ganiban; Annemarie Stroustrup; Judy L. Aschner; Leonardo Trasande; Sean C.L. Deoni; Amy J. Elliott; et al. (Environmental Research, 2024)

The effects of stem bromelain on the gelation behavior of kappa carrageenan under linear and nonlinear rheological regimes - Wilfred V. Rios; Lester C. Geonzon; Arlyn M. Roque; Ma Roxan B. Abiquibil; Mary Diane A. Pilapil; Mark Adones P. Lingaro; Hyacinth N. Suarez; Raymund Lee Antonio C. Sarmiento; Shingo Matsukawa; Rommel G. Bacabac (Food Hydrocolloids, 2024)

The Temnocephalidae (Platyhelminthes): molecular data illuminate the evolution of an ancient group of symbiotic flatworms - David Blair; Lester R.G. Cannon; D. Timothy J. Littlewood; Peter D. Olson; Kim B. Sewell (Systematics and Biodiversity, 2023)

Recognition of whole-landscape changes due to extreme rain events in a hyperarid desert - Lester Olivares; Teresa E. Jordan; William D. Philpot; Rowena B. Lohman (Remote Sensing Applications: Society and Environment, 2023)

Age-dependent effects of social isolation on mesolimbic dopamine release - Megan A. McWain; Rachel L. Pace; Patricia A. Nalan; Deranda B. Lester (Experimental Brain Research, 2022)

From collocations to call-ocations: using linguistic methods to quantify animal call combinations - Alexandra B. Bosshard; Maël Leroux; Nicholas A. Lester; Balthasar Bickel; Sabine Stoll; Simon W. Townsend (Behavioral Ecology and Sociobiology, 2022)
Emerging data in a range of non-human animal species have highlighted a latent ability to combine certain pre-existing calls together into larger structures. Currently, however, the quantification of context-specific call combinations has received less attention. This is problematic because animal calls can co-occur with one another simply through chance alone. One common approach applied in language sciences to identify recurrent word combinations is collocation analysis. Through comparing the co-occurrence of two words with how each word combines with other words within a corpus, collocation analysis can highlight above chance, two-word combinations. Here, we demonstrate how this approach can also be applied to non-human animal signal sequences by implementing it on artificially generated data sets of call combinations. We argue collocation analysis represents a promising tool for identifying non-random, communicatively relevant call combinations and, more generally, signal sequences, in animals. Significance statement Assessing the propensity for animals to combine calls provides important comparative insights into the complexity of animal vocal systems and the selective pressures such systems have been exposed to. Currently, however, the objective quantification of context-specific call combinations has received less attention. Here we introduce an approach commonly applied in corpus linguistics, namely collocation analysis, and show how this method can be put to use for identifying call combinations more systematically. Through implementing the same objective method, so-called call-ocations, we hope researchers will be able to make more meaningful comparisons regarding animal signal sequencing abilities both within and across systems.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Sleep Disordered Breathing in Hypertrophic Cardiomyopathy - Salma I. Patel; Fadi E. Shamoun; Heidi Esser; Sairam Parthasarathy; Michael J. Ackerman; Jeffrey B. Geske; Steve R. Ommen; William T. Love; Virend K. Somers; Anwar A. Chahal; Johan M. Bos; Stephen S. Cha; et al. (Sleep and Vigilance, 2020)

Cerebellar Modulation of Mesolimbic Dopamine Transmission Is Functionally Asymmetrical - Zade R. Holloway; Nick B. Paige; Josiah F. Comstock; Hunter G. Nolen; Helen J. Sable; Deranda B. Lester (The Cerebellum, 2019)

A metatranscriptomic survey of the invasive yellow crazy ant, Anoplolepis gracilipes, identifies several potential viral and bacterial pathogens and mutualists - M. Cooling; M. A. M. Gruber; B. D. Hoffmann; A. Sébastien; P. J. Lester (Insectes Sociaux, 2017)

Equine Pulmonary Cryptococcosis: A Comparative Literature Review and Evaluation of Fluconazole Monotherapy - C. J. Secombe; G. D. Lester; M. B. Krockenberger (Mycopathologia, 2017)

Chimpanzees (Pan troglodytes) Flexibly Use Introduced Species for Nesting and Bark Feeding in a Human-Dominated Habitat - Maureen S. McCarthy; Jack D. Lester; Craig B. Stanford (International Journal of Primatology, 2017)

Stock assessment in inland fisheries: a foundation for sustainable use and conservation - K. Lorenzen; I. G. Cowx; R. E. M. Entsua-Mensah; N. P. Lester; J. D. Koehn; R. G. Randall; N. So; S. A. Bonar; D. B. Bunnell; P. Venturelli; S. D. Bower; S. J. Cooke (Reviews in Fish Biology and Fisheries, 2016)

Groundwater cooling of a supercomputer in Perth, Western Australia: hydrogeological simulations and thermal sustainability - Heather A. Sheldon; Peter M. Schaubs; Praveen K. Rachakonda; Michael G. Trefry; Lynn B. Reid; Daniel R. Lester; Guy Metcalfe; Thomas Poulet; Klaus Regenauer-Lieb (Hydrogeology Journal, 2015)

Population genetic structure of the Australian caddisfly Lectrides varians Mosely (Trichoptera: Leptoceridae) and the identification of cryptic species in south-eastern Australia - S. J. Wickson; E. T. Chester; I. Valenzuela; B. Halliday; R. E. Lester; T. G. Matthews; A. D. Miller (Journal of Insect Conservation, 2014)

What spatial scales are believable for climate model projections of sea surface temperature? - Lester Kwiatkowski; Paul R. Halloran; Peter J. Mumby; David B. Stephenson (Climate Dynamics, 2014)

The distribution and extent of heavy metal accumulation in song sparrows along Arizona’s upper Santa Cruz River - Michael B. Lester; Charles van Riper (Environmental Monitoring and Assessment, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

The conundrum of the yellow crazy ant (Anoplolepis gracilipes) reproductive mode: no evidence for dependent lineage genetic caste determination - M. A. M. Gruber; B. D. Hoffmann; P. A. Ritchie; P. J. Lester (Insectes Sociaux, 2013)

Energetic Charged Particles Above Thunderclouds - Martin Füllekrug; Declan Diver; Jean-Louis Pinçon; Alan D. R. Phelps; Anne Bourdon; Christiane Helling; Elisabeth Blanc; Farideh Honary; R. Giles Harrison; Jean-André Sauvaud; Jean-Baptiste Renard; Mark Lester; et al. (Surveys in Geophysics, 2013)

Parasites as indicators of movement and population connectivity of a non‐diadromous, tropical estuarine teleost: king threadfin Polydactylus macrochir - B. R. Moore; D. J. Welch; S. J. Newman; R. J. G. Lester (Journal of Fish Biology, 2012)
Temporal and spatial patterns in parasite assemblages were examined to evaluate the degree of movement and connectivity of post‐recruitment life‐history stages of a large, non‐diadromous tropical estuarine teleost, king threadfin Polydactylus macrochir , collected from 18 locations across northern Australia. Ten parasites types (juvenile stages of two nematodes and seven cestodes, and adults of an acanthocephalan) were deemed to be suitable for use as biological tags, in that they were considered to have a long residence time in the fish, were relatively easy to find and were morphologically very different to each other which aided discrimination. Univariate and discriminant function analysis of these parasites revealed little difference in temporal replicates collected from five locations, suggesting that the parasite communities were stable over the timeframes explored. Univariate, discriminant function, and Bray–Curtis similarity analyses indicated significant spatial heterogeneity, with Bray–Curtis classification accuracies ranging from 55 to 100% for locations in north‐western and northern Australia, 24 to 88% in the Gulf of Carpentaria, and 39 to 88% on the east coast of Queensland. Few differences were observed among locations separated by P . macrochir in that they indicate a complex population structure across northern Australia. These results should be considered when reviewing the management arrangements for this species.

A multiplex, internally controlled real-time PCR assay for detection of toxigenic Clostridium difficile and identification of hypervirulent strain 027/ST-1 - A. M. Hoegh; J. B. Nielsen; A. Lester; A. Friis-Møller; K. Schønning (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Genotype-dependent effects of adolescent nicotine exposure on dopamine functional dynamics in the nucleus accumbens shell in male and female mice: a potential mechanism underlying the gateway effect of nicotine - Price E. Dickson; Tiffany D. Rogers; Deranda B. Lester; Mellessa M. Miller; Shannon G. Matta; Elissa J. Chesler; Dan Goldowitz; Charles D. Blaha; Guy Mittleman (Psychopharmacology, 2011)

Forestry for the Next Generation - Michael B. Lester (Journal of Forestry, 2011)

Modelling the Long-Term Fate of Mercury in a Lowland Tidal River. I. Description of Two Finite Segment Models - M. Cristina B. Braga; Jason W. Birkett; John N. Lester; George Shaw (Archives of Environmental Contamination and Toxicology, 2010)

Modelling the Long-Term Fate of Mercury in a Lowland Tidal River. II. Calibration and Comparison of Two Models with Field Data - M. Cristina B. Braga; Jason W. Birkett; George Shaw; John N. Lester (Archives of Environmental Contamination and Toxicology, 2010)

Increased amphetamine-induced locomotor activity, sensitization, and accumbal dopamine release in M5 muscarinic receptor knockout mice - Lene S. Schmidt; Anthony D. Miller; Deranda B. Lester; Cecilie Bay-Richter; Christina Schülein; Henriette Frikke-Schmidt; Jürgen Wess; Charles D. Blaha; David P. D. Woldbye; Anders Fink-Jensen; Gitta Wortwein (Psychopharmacology, 2010)

Habitat alteration increases invasive fire ant abundance to the detriment of amphibians and reptiles - Brian D. Todd; Betsie B. Rothermel; Robert N. Reed; Thomas M. Luhring; Karen Schlatter; Lester Trenkamp; J. Whitfield Gibbons (Biological Invasions, 2008)

Assessing phenotypic, biochemical, and molecular diversity in coriander (Coriandrum sativum L.) germplasm - Pedro A. López; Mark P. Widrlechner; Philipp W. Simon; Satish Rai; Terri D. Boylston; Terry A. Isbell; Theodore B. Bailey; Candice A. Gardner; Lester A. Wilson (Genetic Resources and Crop Evolution, 2008)

Periphyton and Macroinvertebrate Assemblage Structure in Headwaters Bordered by Mature, Thinned, and Clearcut Douglas-Fir Stands - Robert J. Danehy; Samuel S. Chan; Gary T. Lester; Russell B. Langshaw; Ted R. Turner (Forest Science, 2007)
We examined the structure of periphyton and macroinvertebrate assemblages in 18 Oregon Coast Range perennial headwater streams bordered by mature (6), clearcut (5), and thinned (7) forest treatments. Summer base flow discharge ranged from 0.02 to1.98 l/s (mean − 0.5 l/s). Periphyton was almost entirely diatoms (72 species) and assemblage characteristics were most strongly influenced by substrate characteristics. Mature treatment sites had fewer species of diatoms and less biomass than other treatments. Diatom richness was highest at sites with higher unit area discharge. Diatom assemblages were dominated by a single species (Achnanthes lanceolata [Brébisson] Grunow), which composed more than 50% relative abundance of the assemblage at nine sites. Macroinvertebrate assemblages were rich, with 194 taxa collected across all sites and 42 taxa found at a single site. Macroinvertebrate assemblages differed across treatments with higher abundance, more Chironomidae taxa, and more biomass at the clearcut treatment sites. We observed no difference in functional feeding group percentage composition across treatments, with collector-gatherers and shredders composing at least 50% abundance at all treatments. We found little difference in either periphyton or macroinvertebrate assemblages between thinned and mature treatments.

Assessing the Relative Severity of Stressors at a Watershed Scale - Lester L. Yuan; Susan B. Norton (Environmental Monitoring and Assessment, 2004)

Stock discrimination and movements of narrow‐barred Spanish mackerel across northern Australia as indicated by parasites - B. R. Moore; R. C. Buckworth; H. Moss; R. J. G. Lester (Journal of Fish Biology, 2003)
The parasite fauna of Spanish mackerel Scomberomorus commerson from 10 sites across northern Australia and one site in Indonesia, was examined to evaluate the degree of movement and subsequent stock structure of the fish. Kupang fish (Indonesia) had very few Terranova spp., Grillotia branchi , Otobothrium cysticum or Pterobothrium sp. compared to Australian fish, indicating that no Australian fish enter the Kupang fishery. Univariate and discriminant function analysis of four ‘temporary’ parasite species, the copepod Pseudocycnoides armatus and the monogeneans Gotocotyla bivaginalis , Pricea multae and Pseudothoracocotyla ovalis , demonstrated little similarity between areas of northern Australia, indicating minimal short‐term exchange between neighbouring groups of S. commerson . Analyses of five ‘permanent’ parasite species, the larval helminths G. branchi , O. cysticum , Pterobothrium sp., Callitetrarhynchus gracilis and Paranybelinia balli , also revealed large differences between areas thus indicating long‐term separation. There are at least six parasitological stocks across northern Australia: Fog Bay/Bathurst Island, Cape Wessel, Groote/Sir Edward Pellew, Mornington Island, Weipa, and the Torres Strait. The occurrence of a few irregular fish in the samples suggested that up to 5% of fish moved between stocks during their lifetime. The similarity of within‐school variability to that between schools showed that the fish do not form long‐term school associations.

Pharmacokinetics of beclomethasone 17-monopropionate from a beclomethasone dipropionate extrafine aerosol in adults with asthma - Lester I. Harrison; Sarala Kurup; Craig Wagner; Bruce P. Ekholm; Julie S. Larson; Harold B. Kaiser (European Journal of Clinical Pharmacology, 2002)

Feed-Forward Regulation of Gibberellin Deactivation in Pea - Robert C. Elliott; John J. Ross; Jennifer J. Smith; Diane R. Lester; James B. Reid (Journal of Plant Growth Regulation, 2001)

The Impact of Logging on Wildlife: A Study in Northeastern Pennsylvania - Todd S. Fredericksen; Brad D. Ross; Wayne Hoffman; Eric Ross; Michael L. Morrison; Jan Beyea; Michael B. Lester; Bradley N. Johnson (Journal of Forestry, 2000)
Seeing and conserving wildlife are among the most important management objectives for nonindustrial private landowners in the eastern United States. Landowners want profitable timber harvests but also want to know how harvesting will affect their wildlife. The study examined associations between stand characteristics and wildlife abundance on 40 stands receiving different logging intensities in northeastern Pennsylvania and found that landowners have some choices when harvesting their stands for retaining or attracting different types of wildlife.

Relative Abundance and Species Richness of Herpetofauna in Forest Stands in Pennsylvania - Brad Ross; Todd Fredericksen; Eric Ross; Wayne Hoffman; Michael L. Morrison; Jan Beyea; Michael B. Lester; Bradley N. Johnson; Nell J. Fredericksen (Forest Science, 2000)
The relative abundance and species richness of herpetofauna was investigated to assess the impact of recent logging operations in 47 forest stands in northeastern Pennsylvania during 1996 and 1997. Stands including nonindustrial private forestlands and public lands that have received some type of harvesting within the last 8 yr ranged from near complete overstory tree cover to complete removal of overstory cover. Stands included the two dominant forest types in the region: northern hardwood (Betula, Fagus, Prunus, Acer, and Tsuga spp.) and oak-hickory/(Quercus and Carya spp.). A total of 8,181 individuals of 26 species (12 salamander, 7 snake, 6 frog, and 1 toad species) were observed in the study stands. The relative abundance and species richness of salamanders increased significantly with increasing retention of tree basal area. Forest stands containing > 15 m²/ha live tree basal area appeared to be a threshold level for high salamander abundance. Snake species abundance and richness increased significantly with increasing removal of tree basal area. The abundance of anuran species showed no significant relationship with amount of tree basal area removal, but the relative abundance and species richness of anurans depended on the presence of water within or bordering the stands. Forest type did not change the overall response of herpetofauna community composition to forest harvesting, although salamanders were more abundant in northern hardwood stands, and snakes were more abundant in oak-hickory stands. Patterns and threshold levels of abundance and species richness of herpetofauna determined in this study may be used to maintain the abundance and richness of selected species when harvesting forest stands. For. Sci. 46(1):139-146.

Sensory cells in the sucker of Craspedella pedum (Plathelminthes, Temnocephalida): in vivo staining with DiO and SEM and TEM observations - B. I. Joffe; Irina V. Solovei; Lester R. G. Cannon (Zoomorphology, 1998)

Anatomy of the sensory nervous system in Craspedella pedum (Plathelminthes, Temnocephalida): DiO staining after fixation and in vivo - B. I. Joffe; Lester R. G. Cannon (Zoomorphology, 1998)

Clean Recycling of Lead‐Acid Batteries for Electric Vehicles: A Reply to Socolow and Thomas - Lester B. Lave; Chris T. Hendrickson; Francis C. McMichael (Journal of Industrial Ecology, 1997)
Summary This article is stimulated by the analysis of Socolow and Thomas in the first issue of this journal. Our work showed that a lead‐acid battery‐powered electric vehicle (Ev) would result in more lead being discharged into the environment than a comparable car burning leaded gasoline. Five hundred thousand EVs would lead to a 20% increase in lead use in the United States, and presumably a comparable 20% increase in lead discharges. The Socolow‐Thomas analysis asserts: (I) choosing not to pursue technology that uses toxic materials will unduly constrain the research and development (R&D) in advanced vehicles and limit the options likely to emerge from that research; (2) we do not do a full risk assessment of the lead discharges from lead smelting, battery making and recycling; and (3) in response to regulation the industry might devise a “clean recycling” system. We doubt the wisdom of increasing R&D on lead batteries because introducing large quantities of lead into cars will pose health risks. The possibility of clean recycling in the future is not an adequate basis for mandating EVs. Proponents of EVs should prove there is no harm to the environment Regulators should not require EVs until there is a reasonable showing of environmental benefit and that the requirement is cost‐effective in reducing ozone.

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)

Toxic element contamination and the occurrence of mercury-resistant bacteria in Hg-Contaminated soil, sediments, and sludges - B. H. Olson; S. M. Cayless; S. Ford; J. N. Lester (Archives of Environmental Contamination and Toxicology, 1991)